Democratic Elections: Strategy to Protect State Civil Apparatus from the Threat of Money Politics and Intimidation in General Elections - Kamaly, Nurul; Zulqiram, Muhammad; Faraidiany, Maghfira; Afrijal, Afrijal (Master Program of Sociology, Universitas Malikussaleh,, 2023)
In a democratic system, the success of general elections is highly dependent on the integrity and neutrality of the State Civil Apparatus (ASN), which is an integral part of organizing fair and free elections. Therefore, it is important to discuss the protection strategy of the ASN in the context of democratic elections. The focus is on addressing two serious threats, namely money politics and intimidation, which often disrupt the integrity of elections. In this case, the researcher seeks to identify efforts that should be taken to protect ASN so that they can carry out their electoral duties reasonably and free from external pressure, which includes various strategies that can be used, including strengthening election-related regulations, increasing ASN awareness about the risks of money politics and intimidation, and the role of election monitoring institutions in supporting election integrity. By implementing this strategy, it is hoped that general elections can become more democratic and have integrity. ASN is also expected to be protected from political money and intimidation threats during the election process.